Hermit Hero in the Context of “New Prose” Social Realism by Maxim Gorky - Gurtueva, Tamara (2021)
It is proved that the works by Maxim Gorky are inseparable from the socio-historical reality of the early XX-th century. Maxim Gorky is a writer, whose work has evolved throughout his career. One of the values in the works by Maxim Gorky is the image of the hero - the hermit, presented in the "Tales of 1922-1924". The semantic space of the hermit hero image exists at the intersection of the semantic fields “social status”, “nature”, “hero image”, “love” and “service to people”.